THE DETERMINATION OF QUALITY AND BRAND IMAGES IN PURCHASING DECISION FOR SMEs CULINARY PRODUCTS - et al., Lucky Hikmat Maulana (International Journal of Advanced Science and Technology, 2020)
Specific culinary is one of the attractions offered and is the center of attention of touristsvisiting a region. The majority of culinary producers are SMEs, which grow and have an impacton intense competition, especially in terms of quality and brand image. This study aims todetermine the effect of product quality and brand image on purchasing decisions on UKMCulinary products. The population in this study was consumers, the dominant culinary beingvarious foods such as cakes, brownies, bread, wet and dry cakes. Non-probabilitysampling method used in determining the sample. The method of data analysis uses multiplelinear regression, correlation, determination, which then continued with the hypothesis test. Theresults showed that product quality and brand image had a positive and significant effect onpurchasing decisions, both simultaneously and partially. It recommended that SMEs promotemore actively through social media, exhibitions, and more stringent supervision of productsafety, and further research carried out using different variables and methods